PROPOSAL FOR PACKAGING DESIGN IMPROVEMENTS USING KANSEI ENGINEERING FOR MSME SNACK PRODUCTS ASSISTED BY PT ENERGI BAYU JENEPONTO (EBJ): USULAN PERBAIKAN DESAIN KEMASAN MENGGUNAKAN KANSEI ENGINEERING UNTUK PRODUK MAKANAN RINGAN MSME DAMPINGAN PT ENERGI BAYU JENEPONTO (EBJ) - Arifin, Suci Ramadhani; Piu, Sriwahyuningsih; Ina Yulianadewi (Universitas Negeri Semarang, 2024)
Zhafran Red Ginger, a small business partner of PT. EBJ, produces healthy ginger-based beverages in Rumbia District, Jeneponto Regency. Currently, their UMKM product faces tough competition from larger companies in the local market. The main issue is its unattractive and outdated packaging design. This research aims to enhance the packaging design using Kansei Engineering methodology, with the hope of attracting more customers and expanding their market presence. The objective is also to support UMKM development in Jeneponto Regency and boost the visibility of local products by improving the marketability of Zhafran Red Ginger's UMKM products.